EFEKTIFITAS SEDIAAN SEDERHANA DAUN SIRIH HUTAN (Piper aduncum L.) TERHADAP HAMA KEPIK (Mictis longicornis) PADA TANAMAN MANGGA - Meidiana, Wika; Budiman, Budiman; Risnawati, Risnawati (Jurnal Pertanian Presisi (Journal of Precision Agriculture), 2024)
Mango is one of the commodities with high economic potential. One of the challenges in mango production is the attack of plant pests. The insect Mictis longicornis is a major pest of mango plants. Its attacks can cause leaves, shoots, or young branches to turn brown, wilt, dry out, and eventually fall off. Control of M. longicornis can be achieved using forest betel leaf powder, which is known to be toxic to several types of insects. The main active compounds in forest betel leaf with insecticidal properties are dilapiol and the piperamidine group. The purpose of this study is to determine the intensity of M. longicornis attacks on mango plants and to analyze the effectiveness of a simple preparation of forest betel leaf powder on the percentage of M. longicornis pest attacks on mango plants. The design used in the study was a Complete Randomized Block Design (CRBD) with a single factor, namely the type of insecticide, with four treatments: control, synthetic insecticide at a concentration of 4 ml/L (active ingredients chlorantraniliprole and thiamethoxam), forest betel leaf powder at concentrations of 7.5%, and 10%. Each concentration of forest betel leaf powder was mixed with distilled water (diluent) containing 0.1% Rinso detergent. The highest attack intensity, 98.51%, was observed in the control treatment (25 days after treatment), while the highest attack intensity before treatment, 90.11%, was observed in the 10% forest betel leaf treatment. Based on descriptive analysis, the application of synthetic insecticide was able to reduce the intensity of M. longicornis pest attacks on mango plants. Based on the Kruskal-Wallis test, the application of synthetic insecticide, 7.5% forest betel leaf powder, and 10% forest betel leaf powder did not significantly differ in the intensity of M. longicornis pest attacks on mango plants.